2013
DOI: 10.1186/2251-6832-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a diesel engine with blends of biodiesel (from a mixture of oils) and high-speed diesel

Abstract: Installation layout of wind turbines plays a prominent role in the design of every wind farm. Thus, the wind farm layout optimization problem is proposed to maximize the total power output with the minimum cost. In this research, Kahrizak region in Tehran province of Iran is selected as a windy region and its real wind speed data are gleaned. Three different scenarios are also considered, with various number of generations and populations for GA parameters, effective distances, and longitude and latitude dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 1 publication
1
30
0
Order By: Relevance
“…The reason for the shorter ignition delay may be the higher cetane number of BLF blends and the higher oxygen content in biodiesel contents of the BLF fuel mixture. This is agreed by Chuah et al [31] who reported that a higher cetane number and higher oxygen content of biodiesel than diesel exhibits a shorter ignition delay time and allows for better combustion of the fuel. Figure 5 shows HRR (heat release rate) corresponding to every crank angle for BLF fuel blends and diesel at maximum engine load conditions.…”
Section: Fuel Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…The reason for the shorter ignition delay may be the higher cetane number of BLF blends and the higher oxygen content in biodiesel contents of the BLF fuel mixture. This is agreed by Chuah et al [31] who reported that a higher cetane number and higher oxygen content of biodiesel than diesel exhibits a shorter ignition delay time and allows for better combustion of the fuel. Figure 5 shows HRR (heat release rate) corresponding to every crank angle for BLF fuel blends and diesel at maximum engine load conditions.…”
Section: Fuel Propertiessupporting
confidence: 81%
“…BSFC was found to decrease with an increase of engine load conditions. This is attributed to the fact that the engine faces fewer amounts of heat losses at higher loads [31]. Figure 7 demonstrates the variations of the brake specific fuel consumption with engine load for petroleum diesel and the blends BLF15, BLF20, and BLF25.…”
Section: Maximum Cylinder Pressurementioning
confidence: 98%
See 1 more Smart Citation
“…However, these fuels are not suitable for compression ignition (CI) engines due to their lower cetane number. Several studies (Ramadhas et al, 2006;Raheman and Ghadge, 2008;Rounce et al, 2012;Ye and Boehman, 2012;Raheman et al, 2013;Dhar and Agarwal, 2014) summarized that biodiesel can be used as alternative fuel in CI engines and it also lower the emissions.…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that BTE improved, smoke opacity; THC and carbon monoxide were reduced. Raheman et al [12] tested soot, performance and emission on a single cylinder diesel engine using biodiesel blends, B10 and B20 obtained from a mixture of mahua and simarouba oils at 50:50 blend ratio with high speed diesel. The results indicated that BSFC and NOx were increased while BTE, CO and HC decreased.…”
Section: Introductionmentioning
confidence: 99%